Au and Pt nanoparticles supported on Ni promoted MoS2 as efficient catalysts for p-nitrophenol reduction. (April 2020) - Akbarzadeh, Elham; Bahrami, Farnaz; Gholami, Mohammad Reza
Graphical abstract: Highlights: A facile method was used to synthesis noble metal NPs on Ni modified MoS2 . Ni atoms on the MoS2 surface exposed more reaction sites for P-NP reduction. Synergistic effect between metal NPs and MoS2 is the origin of excellent catalytic activities. Abstract: In present study, an efficient method was used to synthesis Au and Pt nanoparticles on Ni modified MoS2 (MNi/MoS2 (M = Au and Pt). The morphology and structure of the prepared products were characterized using different microscopic and spectroscopic methods. The as-synthesized MNi/MoS2 nanocomposites were applied for catalytic reduction of p-nitrophenol (P-NP) in the presence of NaBH4 . P-NP is one of the prevalent contaminants in wastewaters, while its corresponding aromatic amine (4-aminophenol) is a precious intermediate for manufacturing of important materials such as pharmaceuticals. The obtained catalytic results indicated that noble metal nanoparticles significantly affect catalytic performance of MoS2 . Synergistic effect between metal nanoparticles and MoS2 was introduced as the origin of this improved catalytic activity of metals decorated MoS2 particles. The enhanced catalytic activity of Ni modified MoS2 particles in comparison to that of unmodified MoS2 nanocomposites emphasis on the role of Ni in catalytic efficiency.